2007
DOI: 10.1038/nrn2201
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fluctuations in brain activity observed with functional magnetic resonance imaging

Abstract: The majority of functional neuroscience studies have focused on the brain's response to a task or stimulus. However, the brain is very active even in the absence of explicit input or output. In this Article we review recent studies examining spontaneous fluctuations in the blood oxygen level dependent (BOLD) signal of functional magnetic resonance imaging as a potentially important and revealing manifestation of spontaneous neuronal activity. Although several challenges remain, these studies have provided insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

142
4,981
5
27

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 6,111 publications
(5,155 citation statements)
references
References 148 publications
142
4,981
5
27
Order By: Relevance
“…Preprocessing consisted of nonbrain‐tissue removal, motion correction, grand mean‐based intensity normalization of the entire 4‐D data set by a single scaling factor, slice timing correction, spatial smoothing with a 6 mm full width at half maximum Gaussian kernel, and temporal bandpass filtering at 0.009 <  f  < 0.15 Hz, which improves BOLD signal estimation and produces connectivity patterns that relate most closely to task‐based activations [Aghajani et al, 2016; Fox and Raichle, 2007; Fransson, 2006; Roy et al, 2009; Toro et al, 2008]. Finally, the RS data were registered to T1‐weighted anatomical images, and subsequently to the 2‐mm Montreal Neurological Institute (MNI) standard space image [Aghajani et al, 2016; Aghajani et al, 2016; Roy et al, 2013].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preprocessing consisted of nonbrain‐tissue removal, motion correction, grand mean‐based intensity normalization of the entire 4‐D data set by a single scaling factor, slice timing correction, spatial smoothing with a 6 mm full width at half maximum Gaussian kernel, and temporal bandpass filtering at 0.009 <  f  < 0.15 Hz, which improves BOLD signal estimation and produces connectivity patterns that relate most closely to task‐based activations [Aghajani et al, 2016; Fox and Raichle, 2007; Fransson, 2006; Roy et al, 2009; Toro et al, 2008]. Finally, the RS data were registered to T1‐weighted anatomical images, and subsequently to the 2‐mm Montreal Neurological Institute (MNI) standard space image [Aghajani et al, 2016; Aghajani et al, 2016; Roy et al, 2013].…”
Section: Methodsmentioning
confidence: 99%
“…Seed‐based whole‐brain iFC analysis implemented within FSL FEAT [Jenkinson et al, 2012], was then employed to reveal BLA and CMA connectivity patterns [Fox and Raichle, 2007]. Specifically, for each participant, and in each hemisphere, a general linear model (GLM) was created that included individual participant's mean time series of BLA and CMA complexes as predictors [Aghajani et al, 2016; Brown et al, 2014; Roy et al, 2013].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NIRS and EEG measurement in a resting condition demonstrated that an increase of oxy‐hemoglobin (O2Hb) was associated with an increase in neuronal responsiveness, whereas a decrease in O2Hb was associated with a decrease in neuronal responsiveness (Butti et al., 2006; Hoshi, Kosaka, Xie, Kohri, & Tamura, 1998). Indeed, it was observed that spontaneous hemodynamic brain activity is not just random noise, but is specifically organized in the resting brain (for a review, see Fox & Raichle, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, studies of cholinergic or serotonergic drug effects also need to consider their extensive modulatory effects [Bargmann, 2012]. This is possible with resting state functional magnetic resonance imaging (RS‐fMRI) in the context of pharmacological stimulation [Fox and Raichle, 2007; Khalili‐Mahani et al, 2014]. …”
Section: Introductionmentioning
confidence: 99%